Purification and characterization of porcine liver DNA polymerase gamma: utilization of dUTP and dTTP during in vitro DNA synthesis. - Mosbaugh, D W (1988)
Porcine liver DNA polymerase gamma has been demonstrated to preferentially incorporate dTMP over dUMP during in vitro DNA synthesis. When polymerase activity was measured in standard reactions containing saturating levels of either dTTP or dUTP, the polymerization rate was slightly faster in the reaction containing dTTP. However, under conditions where both dTTP and dUTP competed, at an equal molar concentration, approximately 3-times more thymine residues were incorporated than uracil residues into DNA. Similarly, preferential incorporation of dTMP was observed on several substrates including poly (dA).oligo p(dT), poly (rA).oligo p(dT) and poly (dA-dT). The discrimination against dUMP incorporation was even more apparent with reduced levels of dUTP. These observations were consistent with the finding that the Km for DNA polymerase gamma was about 3-fold lower for dTTP (0.4 microM) than for dUTP (1.1 microM). On the other hand, the Vmax for these two reactions was very similar. Discrimination against dUMP incorporation was also observed during inhibition of polymerase gamma by dideoxyribonucleoside triphosphates. Dideoxythymidine triphosphate preferentially inhibited dUMP incorporation compared to that of dTMP, whereas ddATP, ddCTP and ddGTP inhibited both reactions equally.